2022
DOI: 10.1136/neurintsurg-2021-018295
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the interventionist’s experience on outcomes of endovascular thrombectomy in acute ischemic stroke: results from the MR CLEAN Registry

Abstract: BackgroundThe relationship between the interventionist’s experience and outcomes of endovascular thrombectomy (EVT) for acute ischemic stroke of the anterior circulation, is unclear.ObjectiveTo assess the effect of the interventionist’s level of experience on clinical, imaging, and workflow outcomes. Secondly, to determine which of the three experience definitions is most strongly associated with these outcome measures.MethodsWe analysed data from 2700 patients, included in the MR CLEAN Registry. We defined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In our study the rate did not differ between different stent models but was numerically higher in the closed-cell LEO+™ stent group. This finding may be explained by the higher mesh density of the LEO+™ compared with the other stents; however, a bias due to the higher frequency of use of this stent at our department combined with greater experience, which is known to be critical for better outcomes in neuroendovascular procedures, cannot be excluded [ 22 ]. Additionally, Pumar et al observed slightly lower rates (73%) of complete occlusion at long-term follow-up [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study the rate did not differ between different stent models but was numerically higher in the closed-cell LEO+™ stent group. This finding may be explained by the higher mesh density of the LEO+™ compared with the other stents; however, a bias due to the higher frequency of use of this stent at our department combined with greater experience, which is known to be critical for better outcomes in neuroendovascular procedures, cannot be excluded [ 22 ]. Additionally, Pumar et al observed slightly lower rates (73%) of complete occlusion at long-term follow-up [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the MR CLEAN Registry data, we have previously shown that a higher CV was associated with better short-term neurological outcomes. 8 Another study also found an association between a higher CV and lower mortality rates. 9 One study compared high- and low-volume centers and demonstrated that patients treated in high-volume centers had higher recanalization rates and higher probabilities of good functional outcomes.…”
Section: Discussionmentioning
confidence: 90%
“…As the consumption of cannabis can cause several cardiac arrhythmias, 44–46 vasospasms, 48 imbalances in coagulation, 7,49,50 protocols to monitor various possible side effects in such patients should be adopted. Furthermore, our study was unable to determine the outcomes of these patients’ thrombectomy based on the centres’ volumes, “door-to-groin” time, and the physicians’ experience, which may have impacted the prognosis of these patients 51–53 …”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, our study was unable to determine the outcomes of these patients' thrombectomy based on the centres' volumes, "doorto-groin" time, and the physicians' experience, which may have impacted the prognosis of these patients. [51][52][53] Our study has some limitations that can be addressed in future studies. The HCUP database could not further categorize cannabis users based on their length of use, frequency of use, and age of first use.…”
Section: Discussionmentioning
confidence: 98%